Contemporary approach to thrombus containing lesions during primary percutaneous coronary interventions in ST-segment elevation myocardial infarction (from the ORPKI National Registry in Poland). (3rd October 2022) - Rakowski, T; Wegiel, M; Malinowski, K; Siudak, Z; Zasada, W; Tokarek, T; Rzeszutko, L; Dudek, D; Bartus, S; Surdacki, A; Dziewierz, A
Abstract: Background: In the era of potent P2Y12 inhibitors, according to current guidelines on ST-segment elevation myocardial infarction (STEMI), treatment with glycoprotein IIb/IIIa inhibitors (GPI) should be limited to selected bail-out or highly thrombotic situations. Similarly, aspiration thrombectomy (AT) is downgraded in current guidelines for very selective but not routine usage. Both recommendations make the treatment of thrombus containing lesions somewhat defensive, underlining the need for an individualized approach to STEMI patients. However, data concerning current clinical practice of such approach are limited. Purpose: We examined the prevalence, procedural characteristics, and predictors of GPI administration and AT usage in all-comers contemporary STEMI patients referred to primary PCI in Poland. Methods: We focused on 116, 873 consecutive STEMI patients undergoing primary PCI in Poland between 2015 and 2020. Results: GPIs were administered in 29.3% of patients and AT was used in 11.6%, with combined treatment with GPI and AT in 6.1% of patients. There was a slight trend towards a decrease in GPI and AT usage during the analyzed years. On the opposite, there was a rapid growth of the ticagrelor/prasugrel usage rate from 6.5% in 2015 to 48.1% in 2020 (Figure 1). Patients with periprocedural GPI administration and combined strategy with GPI and AT were younger, more often men, with history of smoking and presented with cardiogenic shock on admission. They were less likely to have diabetes, chronic kidney disease and previous stroke. Occluded infarct-related artery in baseline angiography and no-reflow during PCI were the strongest independent predictors of GPI administration and combined usage of GPI and AT in a multivariate logistic regression model. Similarly, administration of ticagrelor/prasugrel was an independent predictor of both adjunctive treatment strategies (see table for details). Conclusions: Despite the rapid growth of potent P2Y12 inhibitors usage in Poland in recent years, GPI and AT are selectively used at a stable level during primary PCI in highly thrombotic STEMI lesions. Funding Acknowledgement: Type of funding sources: None.